1994
DOI: 10.1111/j.1526-4610.1994.hed3404230.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Cluster Headache After Carotid Thrombendarterectomy

Abstract: The pathophysiology of cluster headache is largely unknown. One important contributing factor may be an abnormal intracranial-extracranial hemodynamic state. A male patient suffered from chronic left-sided cluster headache for about 15 years. After the institution of lithium therapy the symptoms abated. He was completely free from cluster headache for more than 20 years, until the first postoperative day after a thrombo-endarterectomy for symptomatic 70% carotid stenosis.This case report indicates the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…In this patient, lacking any clinical evidence of a Homer-like syndrome, we found by pharmacological pupillary testing (with phenylephrine and tyramine) evidence of a subclinical ipsilateral sympathetic dysfunction (Bjorne et al, 1994). As we postulated that postganglionic sympathetic nerve dysfunction might be pathophysiologically pertinent, we 352 European Journal of Neurology .…”
Section: Introductionmentioning
confidence: 95%
“…In this patient, lacking any clinical evidence of a Homer-like syndrome, we found by pharmacological pupillary testing (with phenylephrine and tyramine) evidence of a subclinical ipsilateral sympathetic dysfunction (Bjorne et al, 1994). As we postulated that postganglionic sympathetic nerve dysfunction might be pathophysiologically pertinent, we 352 European Journal of Neurology .…”
Section: Introductionmentioning
confidence: 95%
“…It was concluded that the relapse might possibly be secondary to peroperative damage of the carotic sympathetic plexus. 29 By pharmacological testing of the pupil with phenylephrine and tyramine, we found no convincing evidence of a persistent sympathetic dysfunction (Figure 2). The results were equivocal.…”
Section: Clinical Features Of Sellar/suprasellar and Parasellar Pathomentioning
confidence: 99%
“…However, he exhibited manifestations of transient sympathicoparesis, typical of acute attacks of cluster headache. [26][27][28][29] Recently, a patient was reported who, after 20 years of freedom from chronic cluster headache, had a relapse after a carotid thrombendarterectomy. It was concluded that the relapse might possibly be secondary to peroperative damage of the carotic sympathetic plexus.…”
Section: Clinical Features Of Sellar/suprasellar and Parasellar Pathomentioning
confidence: 99%
“…In one case, Bjorne et al [38] reported a patient with a 22-year remission period from CH who experienced attacks on the day after carotid thrombendarterectomy. CLH was similar in all ways to that suffered two decades before and was located on the same side as the arterial vascular surgery.…”
Section: Clh and Cranial Vesselsmentioning
confidence: 99%